2012
DOI: 10.1089/dia.2011.0191
|View full text |Cite
|
Sign up to set email alerts
|

Does Glycemic Variability Impact Mood and Quality of Life?

Abstract: Background: Diabetes is a chronic condition that significantly impacts quality of life. Poor glycemic control is associated with more diabetes complications, depression, and worse quality of life. The impact of glycemic variability on mood and quality of life has not been studied. Methods: A descriptive exploratory design was used. Twenty-three women with type 2 diabetes wore a continuous glucose monitoring system for 72 h and completed a series of questionnaires. Measurements included (1) glycemic control sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
86
3
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 36 publications
(45 reference statements)
2
86
3
6
Order By: Relevance
“…If need be, one can use a "resampling" type of statistical calculation to ensure that the multiplicity of hypotheses being tested are not generating spurious indications of statistical significance due to chance events. 29,30 9. The possibility of differing needs for routine clinical practice and for clinical research.…”
Section: Need To Distinguish Between Measures Of "Glycemic Variabilitmentioning
confidence: 99%
“…If need be, one can use a "resampling" type of statistical calculation to ensure that the multiplicity of hypotheses being tested are not generating spurious indications of statistical significance due to chance events. 29,30 9. The possibility of differing needs for routine clinical practice and for clinical research.…”
Section: Need To Distinguish Between Measures Of "Glycemic Variabilitmentioning
confidence: 99%
“…Anxiety has been reported to be as high as 30-40% in persons with diabetes. 26 Several studies have found the presence of an anxiety disorder to be associated with poor glycemic control for patients with diabetes and researchers have suggested that anxiety disorders may be a risk factor for more di- abetes complications, depression and worse quality of life. 27,28 We found no statistical difference between two groups in terms of GHQ-12 scores.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, exogenous insulin administration results in hunger along with an increased appetite, which is reflected in eating behavior changes. 26 Sodium restriction is the mainstay in treatment of hypertension. A low-salt diet may be expected to cause fluid and electrolyte alterations.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of glycemic variability to longterm outcomes remains controversial, but studies have demonstrated that clinical relevance in glycemic variability is greater in patients with diabetes who experience hypoglycemia, in particular severe hypoglycemia (6)(7)(8)(9)(10). Consequently, diabetes therapies that can lower glycemic variability may also have the potential to reduce the risk of hypoglycemia and improve quality of life (11).…”
mentioning
confidence: 99%